At the limits of the secular : reflections on faith and public life - Barbieri, William A. (Grand Rapids, Michigan Eerdmans Publishing, 2014)
This volume presents an integrated collection of constructive essays by eminent Catholic scholars addressing the new challenges and opportunities facing religious believers under shifting conditions of secularity and'post-secularity.'Using an innovative'keywords'approach, At the Limits of the Secular is an interdisciplinary effort to think through the implications of secular consciousness for the role of religion in public affairs. The book responds in some ways to Charles Taylor's magnum opus, A Secular Age, although it also stands on its own. It features an original essay by David Tracy -- the most prominent American Catholic theologian writing today -- and groundbreaking contributions by influential younger theologians such as Peter Casarella, William Cavanaugh, and Vincent Miller.CONTRIBUTORSWilliam A. Barbieri Jr.Peter CasarellaWilliam T. CavanaughMichele DillonMary DoakAnthony J. GodziebaSlavica JakelicJ. Paul MartinVincent J. MillerPhilip J. RossiRobert J. SchreiterDavid Tracy.
Keywords: Iglesia Católica -- Enciclopedias; Iglesia y Estado -- EEUU; Libros electrónicos